EFEKTIFITAS PELAKSANAAN BIMBINGAN MANASIK HAJI TERHADAP PENINGKATAN KUALITAS IBADAH JAMAAH HAJI (KBIH) JABAL RAHMAH LAMPUNG TIMUR - Savinca, Eka Lidia; Zahrofunnisa, Fatimatus; Bustomi, Ahmad (Multazam : Jurnal Manajemen Haji dan Umrah, 2023)
Guidance on the Hajj rituals is a very important form of service or guidance provided to prospective Hajj pilgrims by the Government as provision or guidance regarding all matters related to the Hajj pilgrimage, so that the pilgrims gain insight or knowledge so that during the implementation they can achieve a prosperous Hajj. The purpose of this research is to find out the effectiveness of the implementation of Hajj ritual guidance on improving the quality of congregational worship carried out by the KBIH Jabal Rahmah Office. The method used in this research is a qualitative descriptive research method, namely research that produces data in the form of words or speech from people or observed behavior. Meanwhile, data collection uses interview methods and also documentation collection. The results of the research were conducted through surveys and data analysis which also involved people who had taken part in the hajj ritual guidance program. The results show that the implementation of guidance involves learning about the hajj. Improving the quality of the hajj is aimed at sincere intentions in performing the hajj, obeying the hajj procedures and rules of the hajj, being patient in facing physical and emotional challenges.